2016
DOI: 10.1093/toxsci/kfw215
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Epigenome with Exposure Effects and Susceptibility: The Epigenetic Seed and Soil Model

Abstract: The epigenome is a dynamic mediator of gene expression that shapes the way that cells, tissues, and organisms respond to their environment. Initial studies in the emerging field of "toxicoepigenetics" have described either the impact of an environmental exposure on the epigenome or the association of epigenetic signatures with the onset or progression of disease; however, the majority of these pioneering studies examined the relationship between discrete epigenetic modifications and the effects of a single env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 106 publications
1
15
0
Order By: Relevance
“…While our data suggest that epithelial cell responses are conserved in a donor-specific fashion, the basis of this ‘programming’ remains to be determined. While it may simply reflect genetic variability, it is possible that epithelial cells may retain an epigenetic imprint of their donor’s life history that can determine future responsiveness 16 . Although the factors that ultimately determine ozone-associated IL-8 induction in epithelial cells are unclear, our findings suggest that the differential activation of MAPKs is likely a part of this programming.…”
Section: Discussionmentioning
confidence: 99%
“…While our data suggest that epithelial cell responses are conserved in a donor-specific fashion, the basis of this ‘programming’ remains to be determined. While it may simply reflect genetic variability, it is possible that epithelial cells may retain an epigenetic imprint of their donor’s life history that can determine future responsiveness 16 . Although the factors that ultimately determine ozone-associated IL-8 induction in epithelial cells are unclear, our findings suggest that the differential activation of MAPKs is likely a part of this programming.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic processes such as DNA methylation and post-translational histone modifications are known to play key roles in memorizing of environmental influences [ 20 , 21 ]. In this way, epigenetic modifications could potentially mediate embedding early social exposure in the genome and provide the long-lasting nature of induced changes in neurobiology and behavior [ 4 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of soil microbial community studies currently ignores plasmids and focuses only on analyses of genomic DNA and often a single gene, such as the ribosomal RNA gene. Even more recently, research in the nascent field of epigenetics has shown that plant markers, such as DNA methylation, are influenced by environmental factors (11). Yet, we are unaware of any studies that have assessed the role of epigenetics in a system with the complexity of organisms found in soil.…”
Section: A Multitude Of Usesmentioning
confidence: 99%